2010
DOI: 10.1021/ef100266p
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Alkyl Ether Sulfonates for Improved Oil Recovery in High-Salinity Carbonate Reservoirs: A Case Study

Abstract: Yibal oil reservoir, a fractured carbonate formation located in the north of Oman and characterized by high salinity brine and high temperatures, is a potential candidate for enhanced oil recovery (EOR) projects. This experimental study focused on the possibility to use surfactant injection as an EOR process in the Yiabl field. On the basis of the results from our previous investigations, ethoxylated sulfonates and amphoteric surfactants were used in this study. Selected surfactants showed a great tolerance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 19 publications
2
51
1
3
Order By: Relevance
“…This equilibrium IFT value is reported for all formulations at various conditions. The dynamic IFT behavior of some surfactants has been reported in many previous studies [2,[29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…This equilibrium IFT value is reported for all formulations at various conditions. The dynamic IFT behavior of some surfactants has been reported in many previous studies [2,[29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 62%
“…For all investigated surfactant concentrations, IFT gradually increased with increasing temperature from 30 • C to 70 • C. Different observations were reported on the effect of temperature on IFT. Aoudia et al [2] reported an increase in the IFT with the increase in temperature. Wu et al [29] observed a decrease in the IFT with temperature using Alfoterra surfactant for n-decane/water system.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A detailed description of the used spinning drop method has been brought elsewhere [28,29]. The IL solution as outer-phase was injected into the glass tube, and 3-4 L crude oil as inner-phase was put into the middle of the tube.…”
Section: Ift Measurementmentioning
confidence: 99%
“…Many surfactants have been proposed as oil displacement agents: ethoxylated and propoxylated sulfates [1], internal olefin sulfonates [2], alkyl ether sulfonates [3], betaine amphoteric surfactants [4], petroleum sulfonates [5], alkyl polyglucoside [6] etc. Petroleum sulfonates are the most widely available and the most inexpensive [7].…”
mentioning
confidence: 99%